Correlating vibrational properties with temperature and pressure dependent CO2 adsorption in zeolitic imidazolate frameworks - A. G. Kontos; Romanos, G.E.; Veziri, C.M.; Gotzias, A.; M. K. Arfanis; Kouvelos, E.; V. Likodimos; Karanikolos, G.N.; P. Falaras (Applied Surface Science, 2020)
Zeolitic imidazolate frameworks (ZIFs) feature a rigid porous structure where the interplay of pore merits and wall functionality, determined by the different imidazolate functional groups, results in superior CO2 capture ability. In this work, the vibrational properties of ZIF-68 and ZIF-69, two characteristic complex gmelinite (GME) type ZIFs comprising of benzimidazolate (bIm) and chloro-benzimidazolate (cbIm) linkers, respectively, were investigated by micro-Raman spectroscopy as a function of CO2 pressure and temperature, in combination with macroscopic adsorption experiments and extended molecular simulations, in order to explore the underlying host-guest interactions and particularly the variation of the framework lattice dynamics and flexibility to CO2 loading. The CO2 isosteric heat of adsorption (Qst) was quantitatively determined by the temperature dependence of the CO2 Fermi dyad intensity at constant pressure. ZIF-69 was consistently found to present higher Qst than ZIF-68 due to the cbIm polar functionality, in close agreement with macroscopic CO2 adsorption experiments and Monte Carlo analysis. More importantly, high CO2 uptake was found to cause significant blue shifts and enhancement of the frequency shift temperature gradients of several low-frequency Raman modes, which according to detailed polarization analysis of ZIF microcrystals, arise from free breathing vibrations of the functionalized ligands in the large ZIF pores. Low-frequency micro-Raman spectroscopy may accordingly constitute a sensitive spectroscopic tool for unveiling lattice dynamics upon CO2 sorption in ZIFs. © 2020 Elsevier B.V.